The Extraction-Non Extraction Conundrum and the Role of Self Ligation in Present Day Mechanotherapy - Dahiya, Sagar; Negi, Gunjan; Arya, Anmol; Chitra, Prasad (Orthodontic Journal of Nepal, 2018)
Rapid technological advancements in the orthodontic field in recent years have enabled clinicians to treat an increasing number of patients using non extraction approaches. Self ligating brackets are becoming increasingly popular as they enable rapid movement of teeth with lateral arch development negating the need to extract teeth. Two Class I malocclusion patients presenting with moderate to severe anterior crowding were treated non-extraction with self ligating fixed appliances. The cases presented illustrate the versatility of self ligating brackets in management of malocclusions with extensive transverse and sagittal components. A review of literature discussing the changing paradigms from extraction to non extraction and use of self ligation is highlighted.